Development of a steady-state microthrust measurement stand for microspacecrafts. (June 2021) - Zhang, Haonan; Duan, Buren; Wu, Lizhi; Hua, Zuohao; Bao, Zijing; Guo, Ning; Ye, Yinghua; DeLuca, Luigi T.; Shen, Ruiqi
Highlights: The null-displacement thrust stand obtains credible and accurate steady-state microthrust data by direct method. The electromagnetic coil collocated with two magnetic sheets can provide calibration force over a wide range. The stand performs well in real tests of both continuous steady-state and throttleable microthrusts. Abstract: A null-displacement thrust stand based on torsional pendulum configuration has been developed to characterize the steady-state microthrust for microspacecrafts. A pair of elastic transducers are applied to constrain the rotation of pendulum arm, so that the stand can maintain static with a small deflection under the loading thrust. The thrust can be obtained according to its linear relationship with the displacement difference with respect to the deflection, which can be detected by a laser displacement sensor. The thrust calibration is implemented via an electromagnetic coil collocated with a pair of permanent magnetic sheets. The repeatability, response time, position drift, noise, resolution and measuring range of the stand are analyzed. The stand features the resolution of 0.1 mN and the maximum available thrust of 2.7 N. Exhibiting the uncertainty less than 12.36%, both steady-state and throttleable thrusts produced by a laser-augmented combustion micromotor are characterized utilizing this stand.